7x-(2x+7)=8x-46

Simple and best practice solution for 7x-(2x+7)=8x-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-(2x+7)=8x-46 equation:


Simplifying
7x + -1(2x + 7) = 8x + -46

Reorder the terms:
7x + -1(7 + 2x) = 8x + -46
7x + (7 * -1 + 2x * -1) = 8x + -46
7x + (-7 + -2x) = 8x + -46

Reorder the terms:
-7 + 7x + -2x = 8x + -46

Combine like terms: 7x + -2x = 5x
-7 + 5x = 8x + -46

Reorder the terms:
-7 + 5x = -46 + 8x

Solving
-7 + 5x = -46 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-7 + 5x + -8x = -46 + 8x + -8x

Combine like terms: 5x + -8x = -3x
-7 + -3x = -46 + 8x + -8x

Combine like terms: 8x + -8x = 0
-7 + -3x = -46 + 0
-7 + -3x = -46

Add '7' to each side of the equation.
-7 + 7 + -3x = -46 + 7

Combine like terms: -7 + 7 = 0
0 + -3x = -46 + 7
-3x = -46 + 7

Combine like terms: -46 + 7 = -39
-3x = -39

Divide each side by '-3'.
x = 13

Simplifying
x = 13

See similar equations:

| 8+8=a | | (3x+18)(3x+18)=36 | | 4-2a=m | | 3x^2-12x+2x-8= | | 8x-(4x+6)=10 | | (3n+2)=0 | | 2(7x-1)=29 | | x^2+14=9x | | -3x+5=-3 | | -75y+.25=.50 | | 4x+2=21 | | (2a-4)=m | | -q+5=10 | | p+.30p=666666667 | | K-3k+3=11 | | 9y^2-y= | | -y-3=8 | | 7d-13=17+3d | | 3(x+1)-7=20 | | 4x^2+7x=0 | | -x+100=100 | | 7(v+17)=6v | | -m+2=1 | | 3a+(2-2a)=a+2 | | -7=-c-29 | | x^2-9x+7=0 | | -5t^2+60t= | | -b+6=-16 | | 4(z-5)+2=z+3 | | 6x^2-22xy-12Y^2=0 | | 16x^5y^3+36x^3y^5= | | -(-3x+w)-4(2w+4x)= |

Equations solver categories